CORPORATE BRAND VALUE DAN NILAI SAHAM PERUSAHAAN - Eni Indriani; Nina Karina Karim; Robith Hudaya; Widyastuti Widyastuti; Yusli Mariadi (Jurusan Akuntansi Fakultas Ekonomi Dan Bisnis Universitas Mataram, 2018)
Investment in a company is expected to provide a profitable return and has an increasing share value. This study aims to determine the effect of trademarks on the value of the company's share. Furthermore, this research is developed to analyze the influence of brand value on the company's stock performance in the banking industry which is ranked in 100th of Indonesia's Most Valuable Brand. The results of this study found that the independent variable (brand value) has a significance value under 0.05 to the dependent variable (share value) with a positive direction. So it can be concluded that the trademark has a positive effect on the value of the company's shares on banking sector in Indonesia. This can be interpreted that the higher the value of the trademark, the higher the value of the company's stock.